LMNA Sequences of 60,706 Unrelated Individuals Reveal 132 Novel Missense Variants in A-Type Lamins and Suggest a Link between Variant p.G602S and Type 2 Diabetes - Florwick, Alyssa; Dharmaraj, Tejas; Jurgens, Julie; Valle, David; Wilson, Katherine L. (Frontiers in Genetics, 2017)
Mutations in LMNA, encoding nuclear intermediate filament proteins lamins A and C, cause multiple diseases (‘laminopathies’) including muscular dystrophy, dilated cardiomyopathy, familial partial lipodystrophy (FPLD2), insulin resistance syndrome and progeria. To assess the prevalence of LMNA missense mutations (‘variants’) in a broad, ethnically-diverse population, we compared missense alleles found among 60,706 unrelated individuals in the ExAC cohort to those identified in 1,404 individuals in the laminopathy database (UMD-LMNA). We identified 169 variants in the ExAC cohort, of which 37 (~22%) are disease-associated including p.I299V (allele frequency 0.0402%), p.G602S (allele frequency 0.0262%) and p.R644C (allele frequency 0.124%), suggesting certain LMNA mutations are more common than previously recognized. Independent analysis of LMNA variants via the type 2 diabetes (T2D) Knowledge Portal showed that variant p.G602S associated significantly with type 2 diabetes (p=0.02; odds ratio=4.58), and was more frequent in African Americans (allele frequency 0.297%). The FPLD2-associated variant I299V was most prevalent in Latinos (allele frequency 0.347%). The ExAC cohort also revealed 132 novel LMNA missense variants including p.K108E (limited to individuals with psychiatric disease; predicted to perturb coil-1B), p.R397C and p.R427C (predicted to perturb filament biogenesis), p.G638R and p.N660D (predicted to perturb prelamin A processing), and numerous Ig-fold variants predicted to perturb phenotypically-characteristic protein-protein interactions. Overall, this two-pronged strategy— mining a large database for missense variants in a single gene (LMNA), coupled to knowledge about the structure, biogenesis and functions of A-type lamins— revealed an unexpected number of LMNA variants, including novel variants predicted to perturb lamin assembly or function. Interestingly, this study also correlated novel variant K108E with psychiatric disease, identified known variant p.I299V as a potential risk factor for metabolic disease in Latinos, linked variant p.G602 with type 2 diabetes, and specifically identified p.G602S as a predictor of diabetes risk in African Americans.